Maine and the Arctic: Why Maine Should Develop an Arctic Strategy - Wood, Jonathan (Maine Policy Review, 2020)
Jonathan Wood articulates why Maine’s recent history as an Arctic player and a detached federal administration, coupled with other Near-Arctic subnational entities creating their own Arctic strategies it is a good time for Maine to articulate its own Arctic strategy.